2004
DOI: 10.1897/03-400
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of polychlorinated biphenyl and polycyclic aromatic hydrocarbon bioaccumulation in Mya arenaria on both water column and sediment bed chemical activities

Abstract: The bioaccumulation of polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) by the filter-feeding soft-shell clam Mya arenaria was evaluated at three sites near Boston (MA, USA) by assessing the chemical activities of those hydrophobic organic compounds (HOCs) in the sediment bed, water column, and organisms. Polyethylene samplers were deployed to measure the activities of HOCs in the water column. Sediment activities were assessed by normalizing concentrations with sediment-water sorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 46 publications
6
68
0
Order By: Relevance
“…Passive sampling has been shown by previous studies to be a reliable and robust approach to obtain porewater concentrations of POPs (35)(36)(37)(38)(39)(40) . The detailed methods have been described elsewhere (37) .…”
Section: Tumbling Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Passive sampling has been shown by previous studies to be a reliable and robust approach to obtain porewater concentrations of POPs (35)(36)(37)(38)(39)(40) . The detailed methods have been described elsewhere (37) .…”
Section: Tumbling Experimentsmentioning
confidence: 99%
“…Previous studies have shown that adsorption onto black carbon present in the sediments can greatly reduce the availability of POPs in the porewater (35)(36)(37)(38)(39) . Yet these studies have focused on areas strongly affected by human activities and have not investigated pristine locations such as Antarctic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As described previously, the EqP approach is based on the concept that the dissolved phase contaminant concentration in the sediment interstitial water reflects a chemical's activity and is a good surrogate for the bioavailable concentration [43,55]. To be clear, the interstitial water concentration is not the only exposure an organism living in the sediment experiences.…”
Section: Equilibrium Partitioning Theorymentioning
confidence: 99%